Learning Analysis of Beat and Tempo Materials In Grade I Elementary School - Haerani, Zulpa; Respati, Resa; Mulyadiprana, Ahmad (Genderang Asa: Journal of Primary Education, 2025)
This study aims to examine the process of beat and tempo learning in elementary schools. The research method used is a qualitative approach with a descriptive research type. The subjects of the study were teachers and students at an elementary school in Tasikmalaya Regency. Data collection tehnicques include interviews with teachers regarding the teaching methodes used during the learning process and observations of students during the learning activities. Data analysis was conducted by describing the results of the interviews and observations. The findings revealed that teachers still employed conventional methods in teaching beat and tempo material. The learning methods lacked variety, which affected students’ enthusiasm during the lessons. The study concluded that there are obstacles in muic learning at the elementary school level, particularly in teaching beat and tempo. As a solution, it is necessary to apply more varied teaching methods to optimize music learning in elementary schools.